Triple oxygen and hydrogen isotope data of gypsum from Cyprus - Katharina Deußen; Claudia Voigt; Michael Staubwasser; Carsten Münker; Mohammed El-Shenawy; Swea Klipsch; Daniel Herwartz (PANGAEA, 2024)
Gypsum samples collected in two outcrops located in the Polemi basin, Cyprus, have been analyzed for their triple oxygen and hydrogen isotopic composition. Respective methods are described in the original publication. The oxygen and hydrogen data provided here is derived from the crystal bound H2O within the Gypsum (CaSO4*2H2O), which allows calculating paleo-water isotopic compositions of the mother brine from which this gypsum precipitated during the Messinian Salinity Crisis. Because the isotopic composition of the mother brine is affected by the local hydroclimate at that time, such analyses allow reconstructing paleo-hydroclimate. One aim of the study was to reconstruct paleo-relative humidity of the Messinian Salinity Crisis. For this purpose, the triple oxygen and hydrogen isotope data was fitted to an appropriate isotope model that is based on the Craig and Gordon formula, which provides absolute paleo-relative humidity estimates. Model input and output data are summarized in Table S2.